Practices in the prescription of antiseizure medications: is it time to change? - Lécio Figueira Pinto; Lucas Scárdua Silva; Rafael Batista João; Vinícius Boldrini; Fernando Cendes; Clarissa Lin Yasuda (Arquivos de Neuro-Psiquiatria, 2024)
The treatment of epilepsy has advanced over the past 30 years through the development of new antiseizure medications (ASMs). Unfortunately, not all of them have been approved yet in Brazil, and many are still underused. When comparing new ASMs to older ones, they are generally not more effective in treating epilepsy. However, they offer better tolerability, with fewer interactions and long-term side effects, especially for patients with comorbidities or those requiring polytherapy. Enzyme induction caused by older ASMs is associated with increased cholesterol levels, drug interactions with decreased effects of statins and other cardiovascular medications, anticoagulants, chemotherapy, immunosuppressors, anti-infective agents (including HIV treatment), antidepressants, and contraceptives. Additionally, they can reduce levels of vitamin D and sex hormones, as well as decrease bone density. The increasing concern about these effects during life, especially after prolonged exposure, has led most developed countries to change prescription patterns in favor of new ASMs, particularly levetiracetam and lamotrigine. Both are also considered the safest options for women of childbearing age. Regrettably, the prescription trends in Brazil have remained largely unchanged over time. This can be partially attributed to the slower approval process of ASM and the reluctance of general physicians and neurologists to embrace these new concepts. In this concise review, we highlight the various advantages linked to the new ASM, aiming to promote a shift in the prescription pattern for ASM. The selection of ASM should be customized according to individual characteristics, and practical suggestions for choosing ASMs are provided in this paper.